Faktor Faktor Yang Mempengaruhi Perilaku Seksual Berisiko Pada Remaja Di SMPN 1 Karanggeneng - Destira, Bima; Ekawati, Heny; Utomo, Dias (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Risky sexual behavior among adolescents is a health issue that can have long-term impacts on both physical and psychosocial well-being Objective: to identify The aim of this study was to determine the factors influencing risky sexual behavior among adolescents at SMPN 1 Karanggeneng. Methods: This article design employed a descriptive-analytic method with a cross-sectional approach. The study sample consisted of 100 students selected using a total sampling technique. The variables examined included parental role, peer influence, and social media. Data were collected using validated and reliable questionnaires, then analyzed using Chi-Square and Spearman tests (α ≤ 0.05). Results: The results showed no significant relationship between parental role and risky sexual behavior (p = 0.097), peer influence and risky sexual behavior (p = 0.056), as well as social media and risky sexual behavior (p = 0.092). This indicates that adolescents with inadequate parental supervision, unhealthy social media exposure, and negative peer interactions are at greater risk of engaging in unhealthy sexual behavior Conclusion: of this study is that parental role, peer influence, and social media do not have a significant effect on risky sexual behavior among adolescents at SMPN 1 Karanggeneng.